Comorbidities and COVID-19 severity in pediatric patients: systematic review and meta-analysis - Mas Wishnuwardhana Widjanarko; Mutiara Nindya; Glenn Fernandez; Axel Jovito (Indonesian Pediatric Society, 2022)
Background COVID-19 has spread around the world. Although symptoms in children are often mild, children remain at risk of developing severe or critical forms of COVID-19, especially those with underlying or comorbid medical conditions. Objective To evaluate the association between comorbidities and severity of COVID-19 in pediatric patients. Methods A systematic review was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. We used PubMed and Google Scholar to locate observational studies that involved children with RT-PCR-confirmed COVID-19 with comorbidities and compared them with controls without comorbidities. Studies must also involve children with severe COVID-19 and provide the risk of severe COVID-19 in children with and without comorbidities as outcome. We performed a meta-analysis to estimate the pooled odds ratio (OR) of severe COVID-19 in children with vs. without comorbidities. Results We included 41 observational studies with a total of 285,828 pediatric COVID-19 patients, comprising 9,754 patients with comorbidities and 276,074 controls. The comorbidities indentified included obesity, congenital malformations, neurological disease, and genetic syndromes. Children with comorbidities had a significantly higher risk of developing severe COVID-19 compared to those without (pooled OR 4.07; 95%CI 2.31 to 7.19; P<0.00001). Conclusion The presence of comorbidities increases the risk of severe COVID-19 in children.